Fenomena Fear of Missing Out di Indonesia Sebagai Bentuk Representasi Pemikiran Simmel Mengenai Pertukaran dalam Interaksi Sosial - watunnaba, Nuris (Universitas Mataram, 2025)
The rise of trends towards an item and the fear of being left behind often creates buying and selling behavior that is no longer based on utility or exchange value, but rather through the process of giving meaning to the item, this phenomenon is often referred to as Fear of Missing Out (FOMO) behavior which influences how people subjectively assess goods, so that people tend to make sacrifices in order to follow the FOMO trend to carry out the exchange process. This study aims to explain FOMO behavior through Simmel's framework of thinking about the concept of exchange in social interaction and to find out how this FOMO phenomenon forms the meaning and social symbols produced towards the trend of an item. The method approach in this study is to use a qualitative method with a literature study analysis approach through previous studies that support and discuss similar phenomena. The results of this study indicate that Simmel's thoughts regarding subjective meaning in the concept of exchange are in line with exchange behavior in the modern era which tends to no longer prioritize the utility or exchange value of an item, and this forms an impulsive culture in the exchange process.